Analisis Kinerja Karyawan Ditinjau Dari Gaya Kepemimpinan Dan Budaya Organisasi Dengan Motivasi Sebagai Mediasi Pada PT Bintang Kadiri Kediri - Nirmala Tirta, Nyoman Afinda; Askafi, Eka; Baehaki, Imam (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
The purpose of this research is to examine the effect of leadership style and work culture on employee performance at PT Bintang Kadiri Kediri through motivation as an intervening variable. This research is quantitative, involving exogenous or independent variables, most likely leadership style and work culture. The subjects of this research are employees who work at PT Bintang Kadiri. A total of 48 respondents will be sent the questionnaire by Google Form and hard copy. This research uses data collection methods. Path analysis is the data analysis employed. The result of this study indicate that: (1) The leadership style has no significant influence on the motivation of the employee. (4) The organizational culture has a significant impact on the performance of employees. (5) The employee's motivation is significantly influenced by the job's performance. (6) Leadership style on employee performance through motivation as an intervening variable has an insignificant influence. (7) The organization's culture on employees' performance in the PT Bintang Kadiri through motivations as a variable intervening has a non-significant impact. The advice that can be given based on the results of this research, in order for the performance of employees to remain good, then the company must always maintain and even improve aspects of a good leadership style, the organizational culture aimed at achieving the goals of the organization, as well as a high work motivation for every employee of PT Bintang Kadiri.